2018
DOI: 10.1016/j.envres.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Green spaces are not all the same for the provision of air purification and climate regulation services: The case of urban parks

Abstract: The growing human population concentrated in urban areas lead to the increase of road traffic and artificial areas, consequently enhancing air pollution and urban heat island effects, among others. These environmental changes affect citizen's health, causing a high number of premature deaths, with considerable social and economic costs. Nature-based solutions are essential to ameliorate those impacts in urban areas. While the mere presence of urban green spaces is pointed as an overarching solution, the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(107 citation statements)
references
References 31 publications
2
81
0
5
Order By: Relevance
“…Improving plant diversity in urban areas is imperative for increased urban ecosystem resilience to environmental hazards including and beyond air pollution 7,11,68 . Furthermore, several studies have demonstrated that diversity not only in species but in vegetation type and structure is important for air quality, carbon sequestration and the sustainable provision of diverse ecosystem services 128,130,148 . Discouragement of monoculture planting is another reason for which it was decided that the species in Tables 3 and 4 would not be ranked.…”
Section: Coordinated Recommendations For Enhanced Vegetation Barrier mentioning
confidence: 99%
“…Improving plant diversity in urban areas is imperative for increased urban ecosystem resilience to environmental hazards including and beyond air pollution 7,11,68 . Furthermore, several studies have demonstrated that diversity not only in species but in vegetation type and structure is important for air quality, carbon sequestration and the sustainable provision of diverse ecosystem services 128,130,148 . Discouragement of monoculture planting is another reason for which it was decided that the species in Tables 3 and 4 would not be ranked.…”
Section: Coordinated Recommendations For Enhanced Vegetation Barrier mentioning
confidence: 99%
“…Furthermore, suburban vegetation may not be equitably available to all urban residents [76]. Green intensification of existing urban areas could help to accommodate growing populations while adding new vegetated cover [36], but it is important to consider the types of vegetation that are added to a city, because different types of vegetation have different abilities to provide ecological functions and services [77]. For example, highly manicured parks and vegetated buildings may be added to increase the aesthetic value of dense cities during green intensification, but these vegetation types can have high associated maintenance costs [78,79] and perform only a limited role in providing other ecosystem services such as supporting biodiversity [80,81].…”
Section: Implications Of Global Changes In Vegetation Covermentioning
confidence: 99%
“…Forested natural areas are primarily sustained though natural regeneration, are influenced by successional dynamics, and on death trees often decompose in place. Forested natural areas can support habitat for native plants and animals that require larger patches (Nielsen et al 2013, Soga et al 2014, Salvati et al 2017, offer human health benefits related to nature-based experiences (Müller et al 2018), and have disproportionately high measures of some ecosystem services compared to other types of urban greenspace (Vieira et al 2018). Separate assessments of street trees and forested natural areas have been developed in local municipalities to inform management (Chacalo et al 1994, Galvin 1999), yet are not commonly put into the context of assessments or policy needs of the entire urban forest (Nowak and Greenfield 2018b).…”
Section: Introductionmentioning
confidence: 99%